OBTENÇÃO DE COMPÓSITOS COM CONDUTIVIDADE MISTA ELETRÔNICA-PROTÔNICA PARA CÁTODOS DE CÉLULAS A COMBUSTÍVEL - Kabbas Junior, Tufy (2017)
Due to the need for clean energy, an alternative that has gained worldwide prominence are like fuel cells. As proton conductive ceramics have an operating temperature in the range of 600 to 800 ° C, making them especially interesting for a fuel cell manufacturing. In this way, the objective of this work was to study a peroxide production with mixed proton-electronic conductivity to update as cell cathodes a solid oxide fuel with proton conductivity. These composites are produced using the mechanical mixture from a quality database, which has electronic conductivity in the proportions 25/75, 50/50 and 75/25, sintered at 1400 ° C. The composite 25 / 75 and 75/25 showed to be only of an electronic and ionic conductor (oxygen ions), respectively, showing no mixed-protonic conductivity. The 50/50 composite, through the obtained results, leads to believe that the mixed proton-electronic conductivity occurred.